Oral health care of hospitalized elderly in a Southern Brazilian public hospital (Research, Society and Development, 2022)
Oral health care plays a part in the integral recovery of hospitalized older people. Based on that, this study characterized the oral health care of hospitalized older people in a Brazilian public hospital. Through application of questionnaires, this cross-sectional study assessed oral health care practice by hospital nursing staff (n=31), companions (n=134) and hospitalized older people (n=200) of a public hospital in Southern Brazil. Clinical examination was conducted by two previously calibrated examiners to screen the oral health condition of the patients, considering the presence of cavitated lesions, residual roots, visible biofilm, calculus, gum inflammation and bleeding. Data were analysed descriptively. Nursing staff limits oral health assessment to surgical procedures; 55% of nurses and 58% of companions do not supervise the oral hygiene, but 81% and 96%, respectively, claim to perform oral hygiene of elderly with difficulties to do so. The elderly (51%) claimed to brush their teeth 3x/day or more; yet, their oral health was characterized by the presence of visible biofilm, calculus, gingival inflammation and bleeding and decayed teeth. Oral health advisory or assessment is not part of the hospital routine. Companions and hospital nursing staff are willing to receive oral health care information. Poor oral health was observed in hospitalized older people, which would probably be enhanced by an interdisciplinary educational approach towards oral health care to older patients.